TINDAKAN ORANG TUA MELAKUKAN SUNAT PADA ANAK PEREMPUAN DI KELURAHAN UKUI KECAMATAN UKUI KABUPATEN PELALAWAN - ", Safitri; ", Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
One of the people who still practice female circumcision is the Ukui Village community, Ukui District, Pelalawan Regency. The existence of female circumcision is a form of assumption that applies in society as a habit that cannot be abandoned because it is one of the religious orders, especially in Islam. This study aims to find out why people in Ukui Village still carry out female circumcision and how the process of implementing female circumcision in Ukui Village is. This study uses a qualitative method and uses a purposive sampling technique. Collecting data using observation, interviews, and documentation. The author discusses this research using Talcott Parsons' Structural Functional Theory (AGIL). The results of this study indicate that all parents in Ukui Village still carry out circumcision on girls and have become part of community life. Female circumcision is carried out to maintain the cleanliness of the genitals and its implementation is more based on religious teachings. The process of implementing female circumcision is carried out in three stages, namely the preparation stage, the implementation stage, and the post-female stage. The process of implementing female circumcision is carried out by midwives and its implementation is carried out simply.Keywords: Parental Action, Female Circumcisio